The Ethnography Study of Tablighi Jamaat’s Da’wah Communication in the Symbolic Interactionism Perspective - Joni Rusdiana; Prahastiwi Utari (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) IAIN Pekalongan, 2019)
This article aims to see how the three premises of Blumer's Symbolic Interactionism are able to explain the phenomenon of the Tablighi Jamaat preaching in the form of khuruj and jaulah. The question to be answered in this article is how Tablighi Jamaat interprets the concept of da'wah (preaching), how the meaning constructed and how the meaning maintained or modified. Using the ethnographic method, this study looks at how the three premises of Blumer Symbolic Interactionism work. Based on the findings and results of the analysis, it was found that the construction of the meaning of da'wah in the Tablighi Jamaah was very different from the general understanding of the community. According to the Tablighi Jamaat, da’wah is not a lecture but invites others to obey the rules of Islam. The main purpose of da'wah according to the Tablighi Jamaat is not to improve others but to improve themselves and is obligatory for every Muslim. This series of meaningful constructs has been built since the beginning of this movement, started by Maulana Ilyas. Long before Maulana Ilyas chose and maintained the madrasa as a method of da'wah while continuing to evaluate it to the conclusion that madrasas were not the right solution to improve society as a whole. Furthermore, he applied the methods of da'wah and tabligh which he obtained not from social interaction, but obtained from God's inspired inspiration. Thus, in this phenomenon, the perspective of Blumer Symbolic Interactionism seems to be limited and unable to explain it thoroughly.